Cost‐effectiveness implications of increasing the efficiency of the extended‐release naltrexone induction process for the treatment of opioid use disorder: a secondary analysis. (21st May 2021) - Murphy, Sean M.; Jeng, Philip J.; McCollister, Kathryn E.; Leff, Jared A.; Jalali, Ali; Shulman, Matisyahu; Lee, Joshua D.; Nunes, Edward V.; Novo, Patricia; Rotrosen, John; Schackman, Bruce R.
Abstract: Background and Aims: In a US randomized‐effectiveness trial comparing extended‐release naltrexone (XR‐NTX) with buprenorphine–naloxone (BUP‐NX) for the prevention of opioid relapse among participants recruited during inpatient detoxification (CTN‐0051), the requirement to complete opioid detoxification prior to initiating XR‐NTX resulted in lower rates of initiation of XR‐NTX (72% XR‐NTX versus 94% BUP‐NX). Design: This was a retrospective secondary analysis of CTN‐0051 trial data, including follow‐up data over 24–36 weeks. Setting: Eight community‐based, inpatient‐detoxification and follow‐up outpatient treatment facilities in the United States. Participants: A total of 283 participants randomized to receive XR‐NTX. Measurements: Efficiency was estimated using a multivariable generalized structural equation model to explore simultaneous determinants of XR‐NTX induction and induction duration (detoxification + residential days). Cost‐effectiveness was estimated from the health‐care sector perspective and included expected costs and quality‐adjusted life‐years (QALYs). Findings: Treatment site was the only modifiable factor that simultaneously increased the likelihood of XR‐NTX induction and decreased induction duration. Incorporating the higher predicted probability of XR‐NTX induction, and fewer predicted days of detoxification and subsequent residential treatment into the cost‐effectiveness framework, reduced the incremental average 24‐week total cost of XR‐NTX treatment from 5317 more than that of BUP‐NX ( P = 0.01) to a non‐statistically‐significant difference of 1016 ( P = 0.63). QALYs gained remained similar across arms. Conclusion: Adopting an efficient model of extended‐release naltrexone initiation could result in extended‐release naltrexone and buprenorphine–naloxone being of comparable economic value from the health‐care sector perspective over 24–36 weeks for patients seeking treatment for opioid use disorder at an inpatient detoxification facility.